النشأة والتكوين والبدايات الدينية للبابا شنودة الثالث حتى الرسامة بابا للكنيسة - الجعلي، أحمد محمد فتحي أحمد (جامعة عين شمس - مركز بحوث الشرق الأوسط, 2023)
يعد البابا شنودة الثالث أحد أبرز من التحقوا بخدمة الكنيسة القبطية، فقد وجد في نفسه الشجاعة والقدرة على الإصلاح وإخراج الكنيسة من عزلتها، لتصبح مؤسسة دينية قادرة على الانفتاح والتواصل مع متطلبات العصر، وهو أحد مؤسسي الاتجاه الكنسي الشمولي الذي يرى أن المسيحية دين ودولة وأن الكنيسة مكلفة بأن تقدم حلولا لكل المشاكل، فقد رغب منذ وصوله إلى الكرسي الباباوي في القيام منفردا بدور الممثل الديني والسياسي للأقباط، وفي عصره تنامى دور الكنيسة فصارت علاقة الأقباط بالدولة تمر عبر كنيستهم. ويتناول هذا البحث نشأة البابا شنودة منذ ولادته وظروف تكوينه العلمي والثقافي وصولا إلى بداية اهتمامه بدراسة الدين المسيحي ونشاطه في مدارس الأحد ثم التحاقه بالرهبنة في دير السريان حتى رسامته أسقفا عاما للتعليم، ثم التطرق إلى العلاقة بين الرئيس جمال عبد الناصر والبابا كيرلس السادس. كذلك عرض لبدايات ظهور التيار الجديد من الشباب الجامعي داخل الكنيسة المصرية وظهور دور الأنبا شنودة خلال وجوده بالكاتدرائية أسقفا للتعليم وأسباب صدامه مع البابا كيرلس، وتناول البحث كذلك وفاة الرئيس جمال عبد الناصر وتولي الرئيس السادات رئاسة الجمهورية، ثم وفاة البابا كيرلس ومراسم تولى البابا شنودة كرسي الباباوية وما أحاط بها من إجراءات كنسية، ورأي السادات وبعض السياسيين في البابا الجديد، ثم تناول بدايات الظهور السياسي للبابا شنودة ورأي الأب متى المسكين في تدخل الكنيسة في السياسة. Pope Shenouda III is considered one of the most prominent people who joined the service of the Coptic Church. He found the courage and the ability to reform and get the church out of its isolation. to become a religious institution capable of splitting apart. He is one of the founders of the totalitarian ecclesiastical trend that sees Christianity as a religion and a state and that the Church is charged with providing solutions to all problems and answers to all questions related to religion and this world. Therefore, his political views were of a direct character. For the Copts, and in his era the role of the church has grown, so the copts, relationship with the state passes through their church and is subject to the relationship between the Pope and the head of state, whether it is friendly or confrontational. This research deals with the rise of Pope Shenouda since his birth and the conditions of his scientific and cultural formation until the beginning of his interest in studying the Christian religion and his activity in Sunday schools, then joining the monasticism in the Syriac monastery until his ordination as a general bishop for education, then addressing the relationship between President Gamal Abdel Nasser and Pope Kyrillos VI. He also presented the beginnings of the emergence of the new trend of university youth within the Egyptian Church and the emergence of the role of Anba Shenouda during his presence in the cathedral as bishop of education and the reasons for his clash with Pope Kyrollos. And the church procedures that surrounded it, and the opinion of Sadat and some politicians about the new pope, then he dealt with the beginnings of the political emergence of Pope Shenouda and the opinion of Father Matta Al-Miskin regarding the church,s intervention in politics.
Keywords: الدين المسيحي -- المؤسسات الدينية -- الكنائس القبطية